Determination of phage susceptibility as a clinical diagnostic tool: A routine perspective - Daubie, Valéry; Chalhoub, Houssein; Blasdel, Bob; Dahma, Hafid; Merabishvili, Maya; Glonti, Tea; De Vos, Nathalie; Quintens, Johan; Pirnay, Jean-Paul; Hallin, Marie; Vandenberg, Olivier (Frontiers in Cellular and Infection Microbiology, 2022)
As the global burden of disease caused by multidrug resistant bacteria is a major source of concern, credible clinical alternatives to antibiotic therapy, such as personalized phage therapy, are actively explored. Although phage therapy has been used for more than a century, the issue of an easy to implement diagnostic tool for determining phage susceptibility that meets current routine clinical needs is still open. In this Review, we summarize the existing methods used for determining phage activity on bacteria, including the three reference methods: the spot test, the double agar overlay plaque assay, and the Appelmans method. The first two methods rely on the principle of challenging the overnight growth of a lawn of bacteria in an agar matrix to a known relative phage to bacteria concentration and represent good screening tools to determine if the tested phage can be used for a “passive” and or “active” treatment. Beside these methods, several techniques, based on “real-time” growth kinetics assays (GKA) have been developed or are under development. They all monitor the growth of clinical isolates in the presence of phages, but use various detection methods, from classical optical density to more sophisticated techniques such as computer-assisted imagery, flow-cytometry, quantitative real-time polymerase chain reaction (qPCR) or metabolic indicators. Practical considerations as well as information provided about phage activity are reviewed for each technique. Finally, we also discuss the analytical and interpretative requirements for the implementation of a phage susceptibility testing tool in routine clinical microbiology.